Biological control of Puto barberi (Hemiptera: Putoidae) with Orius insidiosus (Hemiptera: Anthocoridae) ex situ - De La Torre Bendezú , Cristian (2024)
The objective of the research was to carry out a diagnosis and propose silvicultural treatments in a plantation of Eucalyptus globulus Labill. The methodology was experimental. A census was carried out on 100% of the area (1 ha), which was divided into six subplots. In each subplot, quantitative and qualitative variables were evaluated. It was reported that 100% of the individuals corresponded to E. globulus Labill (1200 individuals). 11 diameter classes were reported, between 8 and 88 cm in diameter at breast height, of which 86.5% are between 8 and 50.99 cm, indicating that the plantation is not yet in the harvesting stage. Regarding the quality of the stem, 63.7% reported a straight stem; While in terms of phytosanitary status, 69.9% were in good condition, 21.8% reported mortality, 6.3% were shoots and 2% were leafless individuals, evidencing the need for treatments. Pruning treatments (1st, 2nd and 3rd) and thinning were proposed for 422 tree individuals to maximize the productivity of the plantation.